Oral disease in relation to future risk of dementia and cognitive decline: Prospective cohort study based on the Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified-Release Controlled Evaluation (ADVANCE) trial - Batty, G.-D.; Li, Q.; Huxley, R.; Zoungas, S.; Taylor, B.-A.; Neal, B.; de Galan, B.; Woodward, M.; Harrap, S.-B.; Colagiuri, S.; Patel, A.; Chalmers, J. (European psychiatry, 2013)
Examine the association of oral disease with future dementia/cognitive decline in a cohort of people with type 2 diabetes. A total of 11,140 men and women aged 55–88 years at study induction with type 2 diabetes participated in a baseline medical examination when they reported the number of natural teeth and days of bleeding gums. Dementia and cognitive decline were ascertained periodically during a 5-year follow-up. Relative to the group with the greatest number of teeth (more than or equal to 22), having no teeth was associated with the highest risk of both dementia (hazard ratio; 95% confidence interval: 1.48; 1.24, 1.78) and cognitive decline (1.39; 1.21, 1.59). Number of days of bleeding gums was unrelated to these outcomes. Tooth loss was associated with an increased risk of both dementia and cognitive decline.